PELATIHAN BERKENDARA SEPEDA MOTOR YANG AMAN, NYAMAN, DAN SELAMAT SESUAI DENGAN UNDANG-UNDANG LALU LINTAS BAGI SISWA SEKOLA MENENGAH KEJURUAN - Bambang Sulistyo; Suhartanta Suhartanta; Ayu Sandra Dewi; Purwanto Purwanto; Muhkamad Wakid; Ibnu Siswanto (LPPM Universitas Bina Bangsa, 2024)
Poor public transportation management makes motorcycles as the most practical and economical choice of transportation for both individuals and families. However, the ease of obtaining a motorbike is not accompanied by awareness of driving well and safely by the rider. Therefore, this community service activity aims to provide safety riding training for vocational school students who are over 17 years old, so they will have more comprehensive riding skills. The activity methods were organized through training, simulations, and practice of safe driving techniques. The training was hold on 11 and 18 May 2024 at the Honda Astra Motor training center, Sudirman street, Yogyakarta. It was attended by 26 students of SMKN 3 Yogyakarta. During the training, participants receive material about safety riding, simulate driving a vehicle using a riding simulator, and riding a motorbike on the safety riding circuit at the training location. The results of the training also showed that participants had increased understanding of safety riding, especially knowledge of speed limits for riding motorbikes in urban areas and the most effective and safe braking techniques to reduce motorbike speed